Assessment of risk management and evaluate the level of risk in construction project: Case Study - Husein, Akeel A; Majdi, Ali (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
This study illustrates the risk assessment and analysis which was made as a requirement in the beginning of the project of a stadium.Risks at project are classified into ten items so that it is easy to manage and monitor them. Simple model is adopted in assessing risks such that it is easy to be understood and modified in contrast with the complex models that produce misleading. Sharing, mitigation and accepting risk are strategies adopted in the final assessment. In the case of sharing risks, it is shown that contracting strategy must be based on risk allocation. Inplanning for risk, purpose must be clear as well as responsibilities and this can be shown precisely in a form of Risk Plan. The objective that this study serves is to identify the cost needed for the whole project from the stage of design to the finishing works. This includes all facilities in the stadium like the concrete frames, buildings and so. The study was very important to provide information to the contractor (a private company) and made confidence in that the estimated cost and time needed for achieving the objectives of the project are realistic and based on sound information.The experience gained from previous similar projects was an advantage factor in that most of problems were clear. The most important problem was the likelihood of delay, which, in the worst case will lead to dramatic increasing in costs. Therefore, the assessment of this risk was principal task in the study although it is necessary to take care for all potential risks.The study shows that risks at construction projects carried by many parties found to be changing according to internal or external changes and the change of priorities can be seen by simulating changes in ranking in each case. It is shown also that badly risk communication leads to real problems as in the case of making thought of building the stadium to be late. The cost of the delay which is the primary risk was calculated for each part of the project. For the construction activities, these were assumed to be the overhead. The time costs calculated was in maximum ( 1,500,000) which is about (10%) of the total cost of the project.